Antimicrobial activity of methanol extracts from different species of the genus Lippia (Research, Society and Development, 2021)
The species of the genus Lippia (Verbenaceae) have several bioactive molecules from their secondary metabolism, which have antimicrobial, analgesic, antifungal and immunomodulatory activities. This study aimed to evaluate the in vitro antimicrobial activity of methanol extract of L. alnifolia, L. origanoides, L. insignis and L. thymoides leaves, against clinically important microorganisms. A phytochemical screening of plant extracts was carried out and the antimicrobial activity was evaluated by the disk diffusion method, in addition to the determination of the minimum inhibitory concentration (MIC) against the bacteria Bacillus subtilis, Escherichia coli, Micrococcus luteus, Pseudomonas aeruginosa, Staphylococcus aureus Salmonella choleraesuis, and the fungi Candida albicans and Candida glabrata. The presence of saponins, terpenes, steroids, coumarins, phenolic acids and flavonoids was observed in the phytochemical evaluation. Methanolic extracts from the leaves of L. alnifolia, L. origanoides and L. insignis showed antimicrobial activity against all tested microorganisms. The methanol extract of L. thymoides showed antimicrobial activity against the microorganisms M. luteus, P. aeruginosa, S. aureus, C. albicans and C. glabrata. Most extracts showed bacteriostatic activity and all extracts showed fungistatic activity for C. albicans and fungicide for C. glabrata. The use of Lippia extracts can be a viable alternative in the treatment of bacterial and fungal infectious diseases.